The information revolution in military affairs in Asia - Goldman, Emily O. (Palgrave Macmillan, 2004)
The contributors to this volume seek to explore the multi-dimensional--institutional, cultural, technological, and political--environments of several Asian states to determine the amenability of those host environments for the adoption and adaptation of the Revolution in Military Affairs (RMA). Using a "diffusion diagnostics" model, the book explores how these countries are trying to address, adapt, and leverage new information technologies to improve and strengthen their militaries.